A Systematic review on aligning efficiency of superelastic NITI: in comparison with conventional NITI and multistranded stainless steel archwires - Kumaran, Deepa; Sundari, Shantha; Chandrasekhar, Shyamala (International Journal of Dental Research, 2017)
Background: The initial leveling and aligning phase of orthodontic treatment involve the use of nickel titanium wires. The nickel titanium wires exhibit unique properties like shape memory and superelasticity. In the beginning, conventional nitinol wires were used, which lacked the superelastic property. Nowadays, superelastic nickel titanium wires are being used commonly. This systematic review aims to evaluate the efficiency of Superelastic NITi in the initial alignment of orthodontic treatment in comparison with conventional NiTi and multistranded stainless steel archwires by measuring the amount of decrowding and the time taken for decrowding.Method: A systematic literature search was performed on Pubmed, Cochrane, Google scholar & Lilacs.Result: Thirty four studies were identified by the search and ten studies satisfied the inclusion criteria and one study was excluded after abstract reading. Finally nine articles were included for quality assessment.Conclusion: This systematic review concluded that there was no significant differences in the aligning efficiency of superelastic NiTi in comparison with conventional NiTi and multistranded stainless steel wires.Â